스케일링 건강보험 급여화에 대한 산재환자의 인식도 - 이혜순; Hea Shoon Lee; 이경희; Kyung Hee Lee (Han'guk Ch'iwisaeng Hakhoe chi, 2013)
Objectives : The purpose of this study is to examine the recognition and needs on the national health insurance coverage of scaling in industry accident injury patients. National health insurance coverage of dental scaling will start in September, 2013. Methods : Subjects were 649 industrial injury patients and they completed self-reported questionnaire. Data were analysed using SPSS version 20.0 for percentage, chi-square test, t-test, ANOVA, post-hoc Scheffe test, and Pearson`s correlation coefficient. Results : Recognition on national health insurance coverage of dental scaling was not fully known to industrial injury patients (24.5%). Highly educated and high income workers seemed to recognize national health insurance coverage of dental scaling (p<.001). Recognition for national health insurance coverage of dental scaling revealed a significance (r=.576, p<.001). Most of the industrial injury workers thought that 50,000 to 100,000 Korean Won of dental scaling fee is reasonable. The coverage of dental scaling should be more than twice over 20 years old. Conclusions : It is necessary to encourage the patients to take regular dental scaling checkup and make them know the health insurance coverage of scaling. The preventive oral health care may improve oral health care and quality of life.